Silicon-based negative electrode material with surface coupling functional layer and preparation method thereof

Through the in-situ self-assembly method of multi-layer surface functional layers, the wetting properties, interface film stability and structural stability of silicon-based anode materials in lithium-ion batteries are solved, and a silicon-based anode material with high specific capacity and excellent circulation performance is achieved, which is suitable for large-scale production.

CN115411246BActive Publication Date: 2025-03-18SHANGHAI INST OF SPACE POWER SOURCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211065399.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-01
Publication Date
2025-03-18
Estimated Expiration
2042-09-01

AI Technical Summary

Technical Problem

Silicon-based negative electrode materials have problems such as wetting, interface film stability and structural stability in lithium-ion batteries, which affect their circulation performance and specific capacity.

Method used

Using the in-situ self-assembly method of multi-layer surface functional layers, an egg-like structure silicon-based anode material with a surface coupling functional layer was synthesized, including graphene hybrid layer, hydrophilic layer and crosslinked M-O layer. Through the coupling connections of these layers, the overall performance of the material is improved.

Benefits of technology

It realizes the high specific capacity, excellent circulation performance and structural stability of the silicon-based negative electrode material, and is simple in process and low in cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115411246B_ABST
    Figure CN115411246B_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon-based negative electrode material with a surface coupling functional layer and a preparation method thereof, wherein the negative electrode material is an egg-like multilayer structure of a silicon-based negative electrode material modified by surface coupling of a graphene hybrid layer / hydrophilic layer / crosslinked M-O layer / hydrophilic layer. The preparation method comprises: step 1, placing a blank silicon-based negative electrode material in a dopamine aqueous solution, stirring, and filtering; step 2, adding the filtered material to a M-containing alcohol salt solution with a concentration of 1 μM / L to 100 μM / L, stirring, and filtering; step 3, adding the filtered material to a dopamine aqueous solution, stirring, and filtering; step 4, adding the filtered material to a 1wt% to 5wt% graphene hybrid solution, stirring, filtering, and drying, and obtaining a silicon-based negative electrode material with a surface coupling functional layer for a lithium-ion battery with a high specific capacity. The present invention provides a silicon-based negative electrode material with a surface coupling functional layer and a preparation method thereof, which has the advantages of excellent cycle performance, simple process, good repeatability, and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a silicon-based negative electrode material with a surface coupling functional layer and a preparation method thereof. Background Art

[0002] Silicon material has high specific capacity and low voltage platform, and is considered to be the negative electrode material for the next generation of high-energy-density lithium-ion batteries. However, silicon's poor conductivity and volume effect are the biggest obstacles limiting its commercial application in the field of high-capacity lithium-ion batteries.

[0003] Silicon has high capacity (3579mAh / g, Li 15 S i4 ), low lithium desorption potential and abundant resources, so it has attracted widespread attention. However, there is a large volume change (300%) during the silicon de- / insertion process, which easily leads to particle pulverization and then falling off the current collector. At the same time, during the charge and discharge process, the continuous fragmentation and generation of the SEI film on the surface of the silicon negative electrode will continuously consume active lithium ions, resulting in a decrease in Coulomb efficiency and battery cycle life.

[0004] In order to solve these problems, researchers have proposed a variety of solutions, such as combining metals, oxides, organic polymers, carbon and other materials with silicon to alleviate its volume changes and improve electrochemical stability. In particular, significant achievements have been made in volume buffering and conductive network structure design, and the energy density, kinetic characteristics and cycle stability of silicon-based composite materials have been greatly improved.

[0005] However, the following issues need to be addressed in the research of high-capacity silicon-based composite materials:

[0006] (1) How to improve the tap density and compaction density of silicon-based materials through nano-microstructure design of materials and ensure the stability of electrode structure under high loading.

[0007] (2) How to reduce the specific surface area while designing the silicon volume buffer and the conductive network structure, or stabilize the SEI film through surface modification to reduce the irreversible capacity of the first cycle.

[0008] The Chinese invention patent application (publication number: CN110504416A) discloses a method for preparing a carbon nanotube-graphene-silicon composite lithium battery material, which uses an ultrasonic mixing method to mix nano silicon and carbon nanotube-graphene to obtain a carbon nanotube-graphene-silicon composite lithium battery material. The material preparation method used in the invention is simple to operate, but only physically mixed silicon-based composite materials are obtained, and the mixture has a single function and cannot solve the problems of material and electrolyte infiltration, interface film stability, and material structure stability.

[0009] The Chinese invention patent application (publication number: CN111668449A) discloses a silicon composite negative electrode material for lithium-ion batteries and a preparation method thereof, which combines the bonding action of the intermediate layer and the cross-linking agent to coat the surface of the silicon-based material with graphene. The coating layer of this invention has a single function and cannot simultaneously solve the problems of silicon-based material infiltration, interface film stability, and structural stability.

[0010] Moreover, the preparation methods of silicon-carbon composite materials reported so far are generally complicated and difficult to apply to large-scale production. Summary of the invention

[0011] The purpose of the present invention is to solve the problems of wettability, interface film stability and structural stability of silicon-based negative electrode materials, and to provide a silicon-based negative electrode material with a surface coupling functional layer for lithium-ion batteries with high specific energy, which has the advantages of high specific capacity, excellent cycle performance, simple process, good repeatability, low cost, excellent cycle performance, etc.

[0012] In order to achieve the above object, the present invention provides a silicon-based negative electrode material with a surface coupling functional layer, the negative electrode material has an egg-like multilayer structure, comprising:

[0013] Silicon-based negative electrode material layer; and

[0014] A functional layer coupled to and formed on the surface of the silicon-based negative electrode material layer;

[0015] The functional layer is composed of a graphene hybrid layer / PDA hydrophilic layer / cross-linked MO layer / PDA hydrophilic layer from the outside to the inside; M is selected from any one or more of Zr, Ti, Si, Mn, Ni, Co, Al, Cr, Mg, Ca, Zn, and Fe.

[0016] Optionally, the hydrophilic layer is selected from at least one of PDA, silane coupling agent, polyethylene glycol, and polyether; the cross-linked MO layer is a polymer obtained by hydrolysis of M alcohol salt; and the thickness of each layer in the functional layer is 10nm-50nm.

[0017] The present invention also provides a method for preparing the silicon-based negative electrode material having a surface coupling functional layer according to the above-mentioned method, comprising:

[0018] Step 1, placing a blank silicon-based negative electrode material in a dopamine aqueous solution, stirring, and filtering;

[0019] Step 2, preparing a M-containing alcohol salt solution with a concentration of 1 μM / L to 100 μM / L, adding the material filtered in step 1 to the M-containing alcohol salt solution, stirring, and filtering;

[0020] Step 3, adding the material filtered in step 2 to the dopamine aqueous solution, stirring, and filtering;

[0021] Step 4, preparing a graphene hybrid solution with a concentration of 1wt% to 5wt%, adding the material filtered in step 3 to the graphene hybrid solution, stirring for 5 to 10 minutes, and filtering; and then vacuum drying at 80°C to 100°C for 0.5 to 48 hours to obtain the silicon-based negative electrode material with a surface coupling functional layer.

[0022] Optionally, in step 1, the concentration of the dopamine solution is 0.01 wt% to 0.5 wt%.

[0023] Optionally, in step 1, the dopamine solution is formed by dissolving dopamine in a tris(hydroxymethyl)aminomethane hydrochloride solution, wherein the concentration of the tris(hydroxymethyl)aminomethane hydrochloride aqueous solution is 0.1 wt% to 0.3 wt%, which plays a buffering role.

[0024] Optionally, in step 1, the pH of the dopamine solution is 7.5 to 9.0 to facilitate the polymerization of dopamine.

[0025] Optionally, in step 2, the M-containing alkoxide comprises: zirconium n-propoxide or aluminum isopropoxide.

[0026] Optionally, in step 3, the concentration of the dopamine solution is 0.01 wt% to 0.5 wt%.

[0027] Optionally, in step 3, the pH of the dopamine solution is 7.5 to 9.0 to facilitate the polymerization of dopamine.

[0028] Optionally, the graphene hybrid is a hybrid of flake graphene and linear carbon nanotubes.

[0029] Beneficial effects of the present invention:

[0030] The present invention synthesizes an egg-like structured silicon-based negative electrode material with a surface coupling functional layer based on the in-situ self-assembly of a multi-layer surface functional layer, which has the advantages of simple process, good repeatability, low cost, and convenience for large-scale production. At the same time, the lithium-ion battery high specific capacity silicon-based negative electrode material with a surface coupling functional layer provided by the method has the advantages of high specific capacity, excellent cycle performance, and stable structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the cycle performance diagram of Si-matrix, Si-matrix@PDA, and Si-matrix@PDA@Zr-O@PDA@GNH materials of Example 1 of the present invention.

[0032] Figure 2a-2c They are respectively Si-matrix ( Figure 2a )、Si-matrix@PDA( Figure 2b) and Si-matrix@PDA@Zr-O@PDA@GNH materials ( Figure 2c ) SEM (scanning electron microscope) image after cycling.

[0033] Figure 3 These are the cycle performance diagrams of Si-matrix, Si-matrix@PDA@Zr-O@PDA@GNH and Si-matrix / PDA / Zr-O / GNH materials of Example 2 of the present invention.

[0034] Figure 4 This is the AC impedance spectra of Si-matrix and Si-matrix@PDA@Zr-O@PDA@GNH materials of Example 3 of the present invention before cycling.

[0035] Figure 5 This is the AC impedance spectra of Si-matrix and Si-matrix@PDA@Zr-O@PDA@GNH materials after cycling in Example 3 of the present invention.

[0036] Figure 6 Graph showing contact angles between Si-matrix, Si-matrix@PDA and Si-matrix@PDA@Zr-O@PDA@GNH materials and electrolytes according to Example 3 of the present invention.

[0037] Figure 7 The charge and discharge curve of Si-matrix@PDA@Zr-O@PDA@GNH of Example 3 of the present invention under the conditions of 0.01V~1.5V. DETAILED DESCRIPTION

[0038] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings.

[0039] The egg-like multilayer structure described in this article is different from the conventional core-shell structure, but is a three-layer structure similar to an egg. The silicon-based negative electrode material is equivalent to the yolk, the cross-linked MO layer is equivalent to the egg white layer, and the graphene hybrid layer is equivalent to the eggshell. The silicon-based negative electrode material and the cross-linked MO layer are connected by a hydrophilic layer PDA, and the cross-linked MO layer and the graphene hybrid layer are connected by a hydrophilic layer PDA.

[0040] The present invention forms a strong chemical bond connection between the silicon-based material and the coating layer through the idea of ​​multi-layer coupling functional layers. The multi-layer coupling functional layers simultaneously solve the problems of wettability, interface film stability, material structure stability, etc. of the silicon-based material, thereby improving the comprehensive performance of the silicon-based negative electrode.

[0041] As used herein, "coupling" has the same meaning as compounding.

[0042] The silicon-based negative electrode material with a surface coupling functional layer provided by the present invention is an egg-like multilayer structure modified by surface coupling of a graphene hybrid layer / hydrophilic layer / crosslinked MO layer / hydrophilic layer (from the outside to the inside), wherein M is selected from any one or more of Zr, Ti, Si, Mn, Ni, Co, Al, Cr, Mg, Ca, Zn, and Fe. The hydrophilic layer is selected from at least one of PDA, a silane coupling agent, polyethylene glycol, and polyether; the crosslinked MO layer is a polymer obtained by hydrolysis of an alcohol salt containing M; and the thickness of each layer in the functional layer is 10nm-50nm.

[0043] The present invention also provides a method for preparing the above-mentioned silicon-based negative electrode material having a surface coupling functional layer, comprising:

[0044] Step 1, preparing a dopamine solution with a concentration of 0.01wt% to 0.5wt%, adjusting the pH to 7.5 to 9.0, placing a blank silicon-based negative electrode material in the dopamine solution, stirring for 5 to 10 minutes, and filtering;

[0045] Step 2, preparing a M-containing alcohol salt solution with a concentration of 1 μM / L to 100 μM / L, adding the material obtained in step 1 to the M-containing alcohol salt solution, stirring for 5 to 10 minutes, and filtering;

[0046] Step 3, preparing a dopamine solution with a concentration of 0.01wt% to 0.5wt%, adjusting the pH to 7.5 to 9.0, adding the material obtained in step 2 to the dopamine solution, stirring for 5 to 10 minutes, and filtering;

[0047] Step 4, preparing a graphene hybrid solution with a concentration of 1wt% to 5wt%, adding the material obtained in step 3 to the graphene hybrid solution, stirring for 5 to 10 minutes, and filtering; then vacuum drying at a temperature range of 80°C to 100°C for a holding time of 0.5 to 48 hours to obtain the silicon-based negative electrode material with a surface coupling functional layer;

[0048] Wherein M is selected from any one or more of Zr, Ti, Si, Mn, Ni, Co, Al, Cr, Mg, Ca, Zn, and Fe. The hydrophilic layer in step 1 is polydopamine (PDA);

[0049] The cross-linked MO layer in step 2 is a polymer obtained by hydrolysis of M-containing alcohol salt.

[0050] The graphene hybrid in step 4 is a hybrid of flake graphene and linear carbon nanotubes.

[0051] Example 1

[0052] Dopamine was dissolved in 0.1wt% tris(hydroxymethyl)aminomethane hydrochloride solution to obtain a dopamine solution with a concentration of 0.02wt%. A blank silicon-based negative electrode material (Si-matrix) was added to the above solution and stirred, and a polymerization reaction of dopamine occurred on the surface of the silicon-based negative electrode material to form a polydopamine layer, which was filtered to obtain Si-matrix@PDA (@ represents composite or load).

[0053] A zirconium n-propoxide solution with a concentration of 1 μM / L was prepared, and the filtered material Si-matrix@PDA was added to the above solution and stirred. The zirconium n-propoxide was hydrolyzed and cross-linked with PDA and itself to form a Zr-O network structure. Si-matrix@PDA@Zr-O was obtained by filtration.

[0054] A 0.1 wt% dopamine aqueous solution was prepared, Si-matrix@PDA@Zr-O was added to the dopamine aqueous solution, stirred to form a dopamine functional layer on the surface, and filtered to obtain Si-matrix@PDA@Zr-O@PDA.

[0055] A graphene hybrid aqueous solution (GNH for short, purchased from Beijing Northern Guoneng Technology Co., Ltd.) with a concentration of 1 wt% was prepared, and the filtered material Si-matrix@PDA@Zr-O@PDA was added to the above GNH solution and stirred. The surface functional groups of the graphene hybrid reacted with the surface functional groups of PDA to form a surface functional layer bonded by chemical bonds. The mixture was filtered and then vacuum dried at 80°C for 24 hours to obtain a silicon-based negative electrode material Si-matrix@PDA@Zr-O@PDA@GNH (layer-by-layer self-assembly) with a surface coupling functional layer.

[0056] At the same time, Si-matrix@PDA materials with only PDA coating layer were prepared, and the cycle performance tests were compared at discharge currents of 0.05C, 0.1C, and 1C. Different discharge currents are used to illustrate the specific capacity of the negative electrode materials at different discharge currents. The cycle performance of Si-matrix, Si-matrix@PDA and Si-matrix@PDA@Zr-O@PDA@GNH materials is shown in Figure 2. Figure 1 As shown in a, the material Si-matrix@PDA@Zr-O@PDA@GNH prepared in this example has the best cycle performance, and its specific capacity is ~1200mAh / g under 1C conditions, proving that it has a high specific capacity. Figure 1 The cycling performance of Si-matrix, Si-matrix@PDA, and Si-matrix@PDA@Zr-O@PDA@GNH obtained by direct mixing is also compared ( Figure 1b). It can be seen that the cycle performance of Si-matrix@PDA@Zr-O@PDA@GNH formed by layer-by-layer self-assembly in the present invention is significantly better than that of Si-matrix@PDA@Zr-O@PDA@GNH formed by direct mixing.

[0057] Figure 2a-2c The SEM (scanning electron microscope) images of the three materials after cycling. The materials prepared by the present invention ( Figure 2c ) The cracks are significantly reduced compared with the control material, and the material structural stability is significantly improved. The structural stability described in this article means the stability of the electrode structure. There is no obvious cracking before and after the cycle. The SEM image after the cycle can prove that the material of the present invention has good structural stability.

[0058] Example 2

[0059] Dopamine was dissolved in a 0.3 wt % tris(hydroxymethyl)aminomethane hydrochloride solution to obtain a dopamine solution with a concentration of 0.05 wt %. A blank silicon-based negative electrode material (Si-matrix) was added to the above solution, stirred and filtered to obtain Si-matrix@PDA; a zirconium n-propoxide solution with a concentration of 5 μM / L was prepared, and the filtered material was added to the zirconium n-propoxide solution, stirred and filtered to obtain Si-matrix@PDA@Zr-O; Si-matrix@PDA@Zr-O was added to a 0.5wt% dopamine aqueous solution, stirred to prepare a dopamine functional layer, and filtered to obtain Si-matrix@PDA@Zr-O@PDA; a graphene hybrid solution (GNH) with a concentration of 3wt% was prepared, and the filtered Si-matrix@PDA@Zr-O@PDA material was added to the above solution, stirred and filtered, and then vacuum dried at 100°C for 24 hours to obtain a silicon-based negative electrode material Si-matrix@PDA@Zr-O@PDA@GNH with a surface coupling functional layer. Si-matrix / PDA / Zr-O / GNH hybrid materials were prepared by conventional mixing methods. The cycle performance of Si-matrix, Si-matrix@PDA@Zr-O@PDA@GNH and Si-matrix / PDA / Zr-O / GNH materials under 1C charge and discharge conditions is shown in Figure 2. Figure 3 As shown, the material prepared by the present invention has the best cycle performance.

[0060] Example 3

[0061] Dopamine was dissolved in a 0.2 wt % tris(hydroxymethyl)aminomethane hydrochloride solution to obtain a dopamine solution with a concentration of 0.02 wt %. A blank silicon-based negative electrode material (Si-matrix) is added to the above solution, stirred and filtered to obtain Si-matrix@PDA; a zirconium isopropoxide solution with a concentration of 1 μM / L isopropanol solution is prepared, and the filtered material Si-matrix@PDA is added to the above aluminum isopropoxide solution, stirred and filtered to obtain Si-matrix@PDA@Zr-O; it is added to a dopamine aqueous solution with a concentration of 0.01wt% to prepare a dopamine functional layer, and filtered to obtain Si-matrix@PDA@Zr-O@PDA; a graphene hybrid solution (GNH) with a concentration of 1wt% is prepared, and the filtered material Si-matrix@PDA@Zr-O@PDA is added to the above GNH solution, stirred and filtered; and then vacuum dried at 90°C for 24h to obtain a silicon-based negative electrode material Si-matrix@PDA@Zr-O@PDA@GNH with a surface coupling functional layer.

[0062] Comparison of the AC impedance spectra of Si-matrix and Si-matrix@PDA@Zr-O@PDA@GNH materials before and after cycling ( Figure 4 , Figure 5 ), the AC impedance of the material prepared in this embodiment before and after the cycle is significantly reduced, indicating that the interface impedance between the material Si-matrix@PDA@Zr-O@PDA@GNH and the electrolyte is optimized, the impedance is reduced, and the stability of the interface film is improved. At the same time, the Si-matrix@PDA material with only a PDA coating layer was prepared. The wettability of Si-matrix, Si-matrix@PDA and Si-matrix@PDA@Zr-O@PDA@GNH materials with the electrolyte is shown in Figure 6 As shown in the figure, the contact angle of the material Si-matrix@PDA@Zr-O@PDA@GNH prepared in this embodiment is reduced, and the wettability with the electrolyte is good. In addition, the charge and discharge curve of the material Si-matrix@PDA@Zr-O@PDA@GNH prepared in this embodiment under the condition of 0.01V~1.5V is as follows Figure 7 shown.

[0063] In some embodiments, M in the cross-linked MO layer may be selected to contain any one of Zr, Ti, Si, Mn, Ni, Co, Al, Cr, Mg, Ca, Zn, and Fe, or a mixture of several of them.

[0064] Theoretically, any silicon-based negative electrode material can be applied to the functional modification of the present invention.

[0065] The preparation method of the silicon-based negative electrode material with high specific capacity and surface coupling functional layer for lithium-ion batteries provided by the present invention is based on the surface self-assembly process to obtain the egg-like structure Si-matrix@PDA@Zr-O@PDA@GNH negative electrode material, without high-temperature heat treatment, to obtain the silicon-based negative electrode material with surface coupling functional layer. The method has simple process, good repeatability, low cost, and is convenient for large-scale production. The silicon-based negative electrode material with surface coupling functional layer of the present invention has high first efficiency, specific capacity and cycle performance in a wide voltage range (0.01~1.5V).

[0066] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A silicon-based negative electrode material having a surface coupling functional layer, characterized in that: The negative electrode material has an egg-like multilayer structure, comprising: Silicon-based negative electrode material layer; and A functional layer coupled to and formed on the surface of the silicon-based negative electrode material layer; The functional layer is composed of a graphene hybrid layer / hydrophilic layer / cross-linked MO layer / hydrophilic layer in order from the outside to the inside; M is selected from any one or more of Zr, Ti, Si, Mn, Ni, Co, Al, Cr, Mg, Ca, Zn, and Fe; The hydrophilic layer is selected from at least one of PDA, silane coupling agent, polyethylene glycol, and polyether; the cross-linked MO layer is a polymer obtained by hydrolysis of M alcohol salt.

2. The silicon-based negative electrode material with a surface coupling functional layer according to claim 1, characterized in that: The thickness of each layer in the functional layer is 10nm-50nm.

3. A method for preparing a silicon-based negative electrode material having a surface coupling functional layer according to claim 1 or 2, characterized in that: The method includes: Step 1, placing a blank silicon-based negative electrode material in a dopamine aqueous solution, stirring, and filtering; Step 2, preparing a M-containing alcohol salt solution with a concentration of 1 μM / L to 100 μM / L, adding the material filtered in step 1 to the M-containing alcohol salt solution, stirring, and filtering; Step 3, adding the material filtered in step 2 to the dopamine aqueous solution, stirring, and filtering; Step 4, preparing a graphene hybrid solution with a concentration of 1wt% to 5wt%, adding the material filtered in step 3 to the graphene hybrid solution, stirring for 5 to 10 minutes, and filtering; and then vacuum drying at 80°C to 100°C for 0.5 to 48 hours to obtain the silicon-based negative electrode material with a surface coupling functional layer.

4. The method for preparing a silicon-based negative electrode material having a surface coupling functional layer according to claim 3, characterized in that: In step 1, the concentration of the dopamine solution is 0.01wt% to 0.5wt%.

5. The method for preparing a silicon-based negative electrode material having a surface coupling functional layer according to claim 4, characterized in that: In step 1, the dopamine solution is formed by dissolving dopamine in a tris(hydroxymethyl)aminomethane hydrochloride aqueous solution, wherein the concentration of the tris(hydroxymethyl)aminomethane hydrochloride aqueous solution is 0.1 wt % to 0.3 wt %.

6. The method for preparing a silicon-based negative electrode material having a surface coupling functional layer according to claim 5, characterized in that: In step 1, the pH of the dopamine solution is 7.5-9.

0.

7. The method for preparing a silicon-based negative electrode material having a surface coupling functional layer according to claim 3, characterized in that: In step 2, the M-containing alkoxide comprises: zirconium n-propoxide or aluminum isopropoxide.

8. The method for preparing a silicon-based negative electrode material having a surface coupling functional layer according to claim 3, characterized in that: In step 3, the concentration of the dopamine solution is 0.01 wt% to 0.5 wt%.

9. The method for preparing a silicon-based negative electrode material having a surface coupling functional layer according to claim 8, characterized in that: In step 3, the pH of the dopamine solution is 7.5-9.

0.

10. The method for preparing a silicon-based negative electrode material having a surface coupling functional layer according to claim 3, characterized in that: The graphene hybrid is a hybrid of flake graphene and linear carbon nanotubes.

Citation Information

Patent Citations

  • Method for preparing carbon nanotube-graphene-silicon composite lithium battery material

    CN110504416A

  • Silicon composite negative electrode material for lithium-ion battery and preparation method thereof

    CN111668449A

  • Negative electrode material, and electrochemical device and electronic device using same

    CN111987296A

  • Silicon-based composite negative electrode material and preparation method thereof, as well as negative electrode and preparation method thereof

    CN112768674A

  • KR20210118317A